Effectiveness Of Behavioral Cognitive Conselvation Using Self Monitoring Techniques Through Setting Lesson Study To Improve Self Order Class X Students Of Hospital Accommodation 2 Singaraja State 2 Vocational School - Agung Darma Putra; Ni Ketut Suarni; I Ketut Dharsana (Department of Guidance and Counseling, FIP, Undiksha, 2019)
This study aims to determine the effectiveness of Behavioral Cognitive Counseling self monitoring techniques to improve the